Atmospheric and Geodesic Controls of Muon Rates: A Numerical Study for Muography Applications - Cohu, Amélie (2022)
Muon tomography or muography is an innovative imaging technique using atmospheric muons. The technique is based on the detection of muons that have crossed a target and the measurement of their attenuation or deviation induced by the medium. Muon flux models are key ingredients to convert tomographic and calibration data into the 2D or 3D density maps of the target. Ideally, they should take into account all possible types of local effects, from geomagnetism to atmospheric conditions. Two approaches are commonly used: semi-empirical models or Monte Carlo simulations. The latter offers the advantage to tackle down many environmental and experimental parameters and also allows the optimization of the nearly horizontal muons flux, which remains a long-standing problem for many muography applications. The goal of this paper is to identify through a detailed simulation what kind of environmental and experimental effects may affect the muography imaging sensitivity and its monitoring performance. The results have been obtained within the CORSIKA simulation framework, which offers the possibility to tune various parameters. The paper presents the simulation’s configuration and the results obtained for the muon fluxes computed in various conditions.